Sunlight-mediated CaO2 inactivation of pathogen indicator organisms in surface water system: Roles of reactive species, characterization of pathogen inactivation. (15th April 2023) - Zhang, Shuwen; Zheng, Ming; Yang, Ge; Zhang, Ting; Magnuson, Jason T.; Chen, Honghong; Zheng, Chunmiao; Qiu, Wenhui
Highlights: CaO2 and sunlight synergistically enhances 75∼ 400% pathogens inactivation. Roles of sunlight (13∼50%), and HRS (68∼87%, OH, 1 O2, OH ‒ etc.) to inactivation. Determine [HRS]SS and second-order reaction rate constants ( k H R S, P ). Determine direct photochemical parameter for pathogen inactivation. Characterize bacterial wall and membrane, viral protein capsid and DNA damage. Abstract: In the era of the current epidemic, it is urgent to control pathogens in sewage, eliminate the source of infection, and optimize the technology for killing pathogens. Combining calcium peroxide (CaO2 ) with sunlight is considered a potentially efficient, economical, and eco-friendly method for pathogen-contaminated water remediation. This paper evaluated the solar activating properties of CaO2 for inactivating pathogenic indicators and explored the roles of reactive species contributing to pathogen inactivation. Moreover, these reactive species' average steady-state concentrations and second-order reaction rate were tentatively explored, and mechanistic model for photoinactivation were establishment. Pathogen's inactivation was mainly attributed to direct photoinactivation (13∼50%) and exogenous indirect mechanisms with corresponding contributions of reactive species, i.e., OH − (14∼23%), 1 O2 (12∼28%), OH (20∼32%), O2 – (12∼16%), and H2 O2 (6∼11%). Furthermore, cell membrane rupture and DNA damage were observed by transmission electron microscopy (TEM) and agarose gel electrophoresis (AGE) experiments. Among experiments on common aqueous constituents influencing photoinactivation, copper and iron ions were found to promote a pathogen-inactivating ability of the system, while fulvic acids (FA) and humic acid (HA) had the opposite effect. This study revealed the potential of CaO2 /sunlight to inactivate pathogens and laid a foundation for its application in inactivating pathogens in surface water. Graphical abstract: Image, graphical abstract